Universitarization of teacher formation in the Colombian Normal School - Rátiva Velandia, Marlén; Lima Jardilino, José Rubens (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: To present the process of universitarization of teacher formation in Colombian Normal Schools. We focus on three elements: teacher professionalization, education system and quality, and its implementation in the Colombian context. Originality/contribution: we describe the elements of universitarization according to which the Colombian public policy was guided to design and implement the transformation of the Normal Schools. This topic has been little addressed in the country. Method: Historical research in which sources were collected and organized (heuristics and doxography). Based on the documentary analysis, Colombian regulations referring to Normal Schools, the General Education Law and higher education regulations were reviewed. The categories identified were contrasted with the theory to establish the understanding (historical synthesis) of the universitarization process in the country. Information strategy/data collection: To collect the information, Colombian legislation since 1970, the time when schools began to be transformed in Latin America, was consulted at the Centro de documentación del Ministerio de Educación Nacional. A review of databases, reflection and research articles, master's and doctoral theses, and books on universitarization and teacher formation was also carried out. Conclusions: The Normal Schools in Colombia have undergone an  universitarization process of teacher formation since the incorporation of the university model, which has led to a change in the institutional organization, naming, curricula, and the funding of the complementary cycle of studies.